A review on thermo-physical properties of bio, non-bio and hybrid nanofluids - Oumer, A. N.; Chen, James Lau Tze; Azizuddin, Abd Aziz (UMP Press, 2019)
The pressure drop and thermal performance of various nanofluids can be affected by their thermo-physical properties. However, there are many different parameters that need to be considered when determining the thermo-physical properties of nanofluids. This paper highlights a detail reviews on the thermo-physical properties of nanofluids with different material type and effect of some process parameters (such as material type, temperature and concentration) on the thermo-physical properties of nanofluids. Four thermo-physical properties mainly density, viscosity, thermal conductivity and specific heat capacity from different literatures were summarized, discussed and presented. The lowest viscosity value of nanofluids in literature was mango bark water-based nanofluid (0.81cP). On the other hand, the maximum thermal conductivity value of nanofluids in the literature was GNP-Ag water-based nanofluid (0.69W/mK). The density and specific heat capacity are strongly dependent on the material type. Meanwhile, the viscosity and thermal conductivity are greatly affected by temperature and concentration. The most influential parameters on thermo-physical properties of nanofluids are material type followed by temperature. Most of the literatures confirmed bio nanofluids have low viscosity value and hybrid have high thermal conductivity values.